A probabilistic approach for cleavage fracture including the statistics of microcracks: Application to a reactor pressure vessel steel. (September 2022) - Ruggieri, Claudio; Jivkov, Andrey P.
Abstract: This work describes a probabilistic framework for cleavage fracture incorporating the measured statistics of microcracks to characterize the cleavage fracture toughness distribution in structural ferritic steels. Fracture toughness testing conducted on standard compact tension C(T) specimens for a 22NiMoCr37 pressure vessel steel, known as the EURO steel A, for varying test temperatures provides the cleavage fracture resistance data needed to determine the experimentally measured J c -distribution. Metallographic examination of etched surfaces for the EURO steel also provides the distribution of carbides, which are assumed as the Griffith fracture-initiating particles, dispersed in the material from which the cleavage fracture toughness distribution is predicted. Overall, the analyses conducted in the present work show that the probabilistic model incorporating the statistics of microcracks holds significant promise as an engineering-level procedure to predict the fracture behavior in structural components with diverse range of temperature and possibly crack-tip constraint. Highlights: Incorporation of measured statistics of microcracks into the probabilistic model. Inclusion of an effective fracture energy into the Griffith criterion. A simplified form of the plastic strain dependence of eligible microcracks. Introduction of a simplified procedure to calibrate the Weibull modulus. The proposed approach removes the temperature dependence of fracture toughness.